DEK proto-oncogene is highly expressed in astrocytic tumors and regulates glioblastoma cell proliferation and apoptosis - Tianda Feng; Yunhui Liu; Chao Li; Zhen Li; Heng Cai (Tumor Biology, 2017)
Astrocytic tumors are the most common neuroepithelial neoplasms with high relapse rate after surgery. Understanding the molecular mechanisms for astrocytic tumorigenesis and progression will lead to early diagnosis and effective treatment of astrocytic tumors. The DEK mRNA and protein expression in normal brain tissues and astrocytic tumors was quantified. To investigate DEK functions in tumor cells, DEK gene was silenced with siRNA in U251 glioblastoma cells. Cell proliferation, cell cycle and apoptosis were then measured. The expression and activity of key genes that regulate cell proliferation and apoptosis were also measured. We identified DEK as a high expressed gene in astrocytic tumor tissues. DEK expression level was positively correlated with the pathological grade of astrocytic tumors. Gene silencing of DEK in U251 glioblastomas inhibited cell proliferation and blocked cells at G0/G1 phase of cell cycle. DEK depletion also induced cell apoptosis, with up-regulated expression of P53 and P21 and down-regulated expression of Bcl-2 and C-myc. The Caspase-3 activity in U251 cells was also significantly increased after knockdown. Our results provided evidences that DEK regulates proliferation and apoptosis of glioblastomas. DEK gene silencing may induce apoptosis through P53-dependent pathway. Our data indicated DEK plays multiple roles to facilitate tumor growth and maintenance. It can be used as a potential target for astrocytic tumor diagnosis and gene therapy.